Canadian expert consensus: management of hypersensitivity reactions to intravenous iron in adults. Issue 4 (2nd April 2019) - Lim, Wendy; Afif, Waqqas; Knowles, Sandra; Lim, Gloria; Lin, Yulia; Mothersill, Charmaine; Nistor, Irina; Rehman, Faisal; Song, Christine; Xenodemetropoulos, Ted
Abstract : Background and Objectives: Rare but potentially life‐threatening hypersensitivity reactions can occur during the administration of intravenous iron. To provide guidance to healthcare professionals caring for adults receiving intravenous iron, a panel of 10 Canadian clinical experts developed a practical algorithm for the identification and management of hypersensitivity reactions to intravenous iron. Materials and methods: A systematic search of PubMed to February 2018 was performed. Articles related to hypersensitivity reactions were selected for review. The algorithm was developed during a 1‐day live meeting based on the literature review and clinical expertise where evidence was lacking. The algorithm was then refined through an iterative process involving a web‐based platform and virtual meetings. Results: The algorithm provides guidance to healthcare professionals in preparing for and administering IV iron, as well as recognizing and managing hypersensitivity reactions to intravenous iron. Considerations for re‐challenging patients who have experienced prior reactions are provided. Conclusion: Healthcare professionals who are involved in the care of patients receiving intravenous iron should be trained to anticipate, recognize and manage hypersensitivity reactions to intravenous iron to optimize patient care.